2021
DOI: 10.1002/hec.4232
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring institutions in healthcare markets: Experimental evidence

Abstract: This paper investigates the impact of monitoring institutions on market outcomes in health care. Healthcare markets are characterized by asymmetric information. Physicians have an information advantage over patients with respect to appropriate treatments, which they may exploit through over-or under-provision or by overcharging. We introduce two types of costly monitoring: endogenous and exogenous monitoring. When monitoring detects misbehavior, physicians have to pay a fine. Endogenous monitoring can be reque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…The present study has shown that monitoring may play a vital role in enhancing communication between physicians and their patients and improving healthcare quality. This result corroborates those of other studies [ 3 , 20 ], indicating that monitoring is an effective method for reducing mistreatment in the healthcare context.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study has shown that monitoring may play a vital role in enhancing communication between physicians and their patients and improving healthcare quality. This result corroborates those of other studies [ 3 , 20 ], indicating that monitoring is an effective method for reducing mistreatment in the healthcare context.…”
Section: Discussionsupporting
confidence: 92%
“…Due to difficult economic conditions and mismanagement, the Jordanian government has become unable to effectively monitor the healthcare system or establish incentives for healthcare providers to increase quality and treat their patients appropriately. As Physicians enjoy an information advantage over patients concerning the appropriate treatment for the patient, it is highly possible that they use their informational advantage to increase personal income by ordering unnecessary tests or using irrelevant techniques or prescribing more expensive medicine despite the existence of cheaper generic medication [ 2 , 3 ]. It is certain that an absence of information interaction between a patient and a physician can produce ineffective outcomes in healthcare systems and preclude a patient from receiving high-quality treatment at a reasonable cost.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a health care framework has an impact on medical decision making in a laboratory setting. This is shown by various experimental studies (e.g., Ahlert et al., 2012; Angerer et al., 2021a; Kairies‐Schwarz et al., 2017; Kesternich et al., 2015).…”
mentioning
confidence: 66%
“…For example, for credence goods markets, Angerer et al. (2021b) and Angerer, Glätzle‐Rützler, et al. (2021) look at the impact of monitoring and feedback platforms on market efficiency, and Greiner et al.…”
Section: Related Literaturementioning
confidence: 99%
“…Typically applying neutral framings, experiments in the credence goods literature showed that overtreatment can be reduced by costly second opinions (Mimra et al, 2016), competition (Huck et al, 2016), and separating treatment from diagnosis and prescription decisions (Greiner et al, 2017). Recent experiments show that monitoring mechanisms with financial consequences reduce overtreatment and the overcharging of patients (Angerer et al, 2021;Hennig-Schmidt et al, 2019;and Groß et al, 2021). We complement these experiments by investigating whether performance-based financial incentives which implicitly rely on monitoring a physician's performance are capable of coping with non-optimal medical service provision such as overtreatment under FFS.…”
Section: Introductionmentioning
confidence: 99%